The Influence Of Work Environment And Teamwork On The Performance Of Employees In The Adidas Division At PT Nikomas Gemilang, Serang, Banten - Titi Susanti; Muhammad Suparmoko; Ende Ende (International Journal of Health Engineering and Technology, 2026)
The work environment and organizational commitment if managed well by the A well-managed work environment and teamwork will motivate employees to perform their jobs optimally. This will ensure employees feel comfortable at work and avoid any thoughts of leaving the company. The purpose of this study was to determine the extent to which the work environment and teamwork influence the performance of employees in the Adidas Division at PT Nikomas Gemilang. The author employed a causal associative method with a quantitative descriptive approach, employing a population-based sampling process and a questionnaire as the primary data collection tool. The data collection technique used a questionnaire administered to 75 (seventy-five) respondents using a Likert scale and SPSS version 26. The results of this study indicate that (1) the work environment partially significantly influences employee performance in the Adidas Division at PT Nikomas Gemilang, as indicated by the calculated t-value > t-table (7.176 > 1.993) and a significance value of 0.000, which is less than the 0.05 threshold. Therefore, Ha is accepted and H0 is rejected. (2) Partially, teamwork significantly influences employee performance in the Adidas Division at PT Nikomas Gemilang, as indicated by the calculated t-value > t-table (6.335 > 1.993) and a significance value of 0.000, less than the 0.05 level. Therefore, Ha is accepted and H0 is rejected. (3) Simultaneously, the work environment and teamwork influence employee performance in the Adidas Division at PT Nikomas Gemilang, as indicated by the calculated F-value > F-table (184.502 > 3.12) with a significance level of 0.000. Therefore, Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that the work environment and teamwork variables, both partially and simultaneously, have a significant influence on employee performance.